Accounting for tutorial teaching assistants’ buy-in to reform instruction - Renee Michelle Goertzen; Rachel E. Scherr; Andrew Elby (Physical Review Special Topics. Physics Education Research, 2009)
Successful implementation of tutorials includes establishing norms for learning in the tutorial classroom. The teaching assistants (TAs) who lead each tutorial section are important arbiters of these norms. TAs who value (buy into) tutorials are more likely to convey their respect for the material and the tutorial process to the students, as well as learning more themselves. We present a case study of a TA who does not buy into certain aspects of the tutorials he teaches and demonstrate how his lack of buy-in affects specific classroom interactions. We would hope to design professional development programs to help TAs appreciate the power of tutorial instruction. However, our research suggests that the typical professional development activities offered to tutorial TAs are not likely to be effective. Instead, it appears that what we call the “social and environmental context” of the tutorials—including classroom, departmental, and institutional levels of implementation—has the potential to strongly affect TA buy-in to tutorials and probably outweighs the influence of any particular activity that we might prepare for them.